TECHNOLOGY FOR MODELING PHYSICOCHEMICAL PROCESSES IN THE PLASMA OF OVERVOLTAGE NANOSECOND GAS DISCHARGE FOR THE SYNTHESIS OF NANOSTRUCTURED THIN FILMS AND ITS SOFTWARE IMPLEMENTATION - BILAK, YURII; SHUAIBOV, OLEKSANDR; BUCHUK, ROMAN; ROL, MARIANA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Context. In this work, for the first time, a technology has been developed based on an integrated physical-mathematical model of the emission spectrum of plasma from an overvoltage nanosecond gas discharge, which is used for the synthesis of nanostructured thin films. Universal software has been developed for modeling plasma parameters and its spectrum, providing interactivity and flexibility for adaptation to various experimental conditions. Visualization of results has been implemented to enhance data analysis and interpretation. The developed software is an effective tool for scientific research and practical applications in plasma physics and materials science. Objective. To develop a technology based on an integrated model and software for analyzing physicochemical processes in the plasma of an overvoltage nanosecond gas discharge for describing the dynamics of plasma parameters, modeling the plasma emission spectrum, optimizing the conditions for the synthesis of nanostructured thin films, and creating a tool for predicting plasma parameters. Method. In the article, a combined theoretical-experimental method is used, which includes key aspects such as mathematical modeling for the implementation of physical and spectral models to describe the main processes in plasma, such as gas ionization, recombination, formation of runaway electrons, electrode erosion, and the formation of clusters of nanostructured films; the use of Boltzmann equations for calculating the distribution of particles over energy levels; calculation of the plasma emission spectrum taking into account temperature, Doppler line broadening, and plasma parameters; representation of spectral lines as Gaussian profiles to describe their width and intensity. The model is implemented based on numerical methods for solving differential equations using the Python programming language for modeling physical processes and visualizing results. Results. The developed technology, the constructed spectra, the numerical modeling conducted, and the developed software confirm the effectiveness of the developed technology based on mathematical modeling for analyzing plasma processes and spectral characteristics. This opens up new possibilities for optimizing plasma technologies and creating innovative materials. Conclusions. The technology for calculating plasma parameters and emission spectra for the experiment has been tested. Special attention has been paid to modeling spectral lines for key elements such as nitrogen (N), oxygen (O), and tungsten (W), using Gaussian functions to reproduce the widths of the spectral lines. The model has been adapted to predict plasma characteristics under conditions of variable discharge parameters, such as electric field intensity, pressure, and temperature. This allows for the optimization of film synthesis processes and the creation of new materials with improved properties. The proposed approach has practical applications in sensing, optoelectronics, photovoltaics, and other advanced technologies. In the future, a promising direction is the improvement of the technology and, accordingly, the software product by creating an interface for convenient control of model parameters, which will allow the use of the program without deep programming knowledge; integration of the program with cloud computing platforms for modeling complex systems with high performance; and the application of machine learning algorithms for automatic optimization of discharge parameters and result prediction.